Effects of a Mutation in the HSPE1 Gene Encoding the Mitochondrial Co-chaperonin HSP10 and Its Potential Association with a Neurological and Developmental Disorder - Bie, Anne S.; Fernandez-Guerra, Paula; Birkler, Rune I. D.; Nisemblat, Shahar; Pelnena, Dita; Lu, Xinping; Deignan, Joshua L.; Lee, Hane; Dorrani, Naghmeh; Corydon, Thomas J.; Palmfeldt, Johan; Bivina, Liga; et al. (Frontiers in Molecular Biosciences, 2016)
We here report molecular investigations of a missense mutation in the HSPE1 gene encoding the HSP10 subunit of the HSP60/ HSP10 chaperonin complex that assists protein folding in the mitochondrial matrix. The mutation was identified in an infant who came to clinical attention due to infantile spasms at three months of age. Clinical exome sequencing revealed heterozygosity for a HSPE1 NM_002157.2:c.217C>T de novo mutation causing replacement of leucine with phenylalanine at position 73 of the HSP10 protein. This variation has never been observed in public exome sequencing databases or the literature. To evaluate whether the mutation may be disease-associated we investigated its effects by in vitro and ex vivo studies. Our in vitro studies indicated that the purified mutant protein was functional, yet its thermal stability, spontaneous refolding propensity, and resistance to proteolytic treatment were profoundly impaired. Mass spectrometric analysis of patient fibroblasts revealed barely detectable levels of HSP10-p.Leu73Phe protein resulting in an almost 2-fold decrease of the ratio of HSP10 to HSP60 subunits. Amounts of the mitochondrial superoxide dismutase SOD2, a protein whose folding is known to strongly depend on the HSP60/HSP10 complex, were decreased to approximately 20% in patient fibroblasts in spite of unchanged SOD2 transcript levels. As a likely consequence, mitochondrial superoxide levels were increased about 2-fold. Although we cannot exclude other causative or contributing factors, our experimental data support the notion that the HSP10-p.Leu73Phe mutation could be the cause or a strong contributing factor for the disorder in the described patient.